Gelation Behavior Study of a Resorcinol–Hexamethyleneteramine Crosslinked Polymer Gel for Water Shut-Off Treatment in Low Temperature and High Salinity Reservoirs - Yongpeng Sun; Yanchao Fang; Ang Chen; Qing You; Caili Dai; Rui Cheng; Yifei Liu (Energies, 2017)
Mature oilfields usually encounter the problem of high watercut. It is practical to use chemical methods for water-shutoff in production wells, however conventional water-shutoff agents have problems of long gelation time, low gel strength, and poor stability under low temperature and high salinity conditions. In this work a novel polymer gel for low temperature and high salinity reservoirs was developed. This water-shutoff agent had controllable gelation time, adjustable gel strength and good stability performance. The crosslinking process of this polymer gel was studied by rheological experiments. The process could be divided into an induction period, a fast crosslinking period, and a stable period. Its gelation behaviors were investigated in detail. According to the Gel Strength Code (GSC) and vacuum breakthrough method, the gel strength was displayed in contour maps. The composition of the polymer gel was optimized to 0.25~0.3% YG100 + 0.6~0.9% resorcinol + 0.2~0.4% hexamethylenetetramine (HMTA) + 0.08~0.27% conditioner (oxalic acid). With the concentration increase of the polymer gel and temperature, the decrease of pH, the induction period became shorter and the crosslinking was more efficient, resulting in better stability performance. Various factors of the gelation behavior which have an impact on the crosslinking reaction process were examined. The relationships between each impact factor and the initial crosslinking time were described with mathematical equations.